POPULATION SIZE CAN MODERATE THE EFFECT OF HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH - Dj, Arifhan Ady; Putra, Agus; Santoso, Agus; Basri, Hasan; Kamal, Irsyad (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This research is a quantitative study with an explanatory approach, namely an approach that uses previous studies as the main basis for obtaining novelty and is developed in the research being conducted. The data used in this study are secondary data from various credible sources, namely the Central Statistics Agency from 2010 to 2024. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show the two hypotheses proposed in this article, namely the Human Development Index variable can have a positive relationship direction and a significant influence on Economic Growth can be accepted and proven. This is because the P-Values are positive and below the significance level of 0.05, namely 0.009. The reason for these results is that the Human Development Index which is influenced by Health and Education Levels can have a good, positive, and significant impact on Economic Growth. On this basis, it can be concluded that the first hypothesis in this article can be accepted. In the next section, the researcher also has another hypothesis, namely that the Population Size variable can moderate the influence of the Human Development Index variable on Economic Growth because of the same thing, namely the P-Values are positive and below the significance level of 0.05, which is 0.000 more significant than direct testing of 0.009. Thus, the first and second hypotheses in this article can be accepted. Keywords: Population Size, Human Development Index, Economic Growth